Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan dan Gaya Hidup Terhadap Minat Beli pada Motor Listrik Volta di Surakarta - Dwi Wahyu Nugroho; Mutya Paramita Pratita (Indo Publishing, 2026)
Electric motorcycles are an environmentally friendly and economical transportation solution in the face of energy scarcity and air pollution. However, there are indications of problems with consumer interest in PT Volta products in Surakarta. Referring to this urgency, this study examines the contribution of perceived benefits, perceived ease of use, and lifestyle in shaping customer purchasing interest. The main objective of this study is to identify and explain the influence of these three variables on the decision of potential consumers of Volta electric motorcycles in Surakarta. This study applies a quantitative approach by utilising primary data as the main source of information. Considering that the population of potential consumers of Volta electric motorcycles in Surakarta cannot be identified with certainty (unknown population), a sample size of 100 respondents was determined. Participants were selected using purposive sampling based on specific criteria. Data collection instruments were integrated through the distribution of questionnaires, literature studies, and field observations. Furthermore, the data were analysed using a series of statistical procedures, including instrument testing (validity and reliability), descriptive analysis, classical assumption testing, and multiple linear regression analysis to test the hypothesis through t-tests, F-tests, and the coefficient of determination (R2). Evaluation of the research instruments showed that all questionnaire items met the validity and reliability criteria. In addition, the model met the classical assumption requirements, as indicated by the absence of multicollinearity and heteroscedasticity, and had normally distributed residuals. The resulting regression model is presented through the following equation: Y = 4.830 + 0.733 X1 + 0.037 X2 + 0.044 X3 + e. Partially (t-test), the results show that only the variable of perceived ease of use has a significant effect on purchase intention. Conversely, the variables of perceived benefits and lifestyle did not show a statistically significant effect. However, simultaneously (F test), the F value of 33.793 with a significance of 0.000 < 0.05 confirmed that this model was suitable (goodness of fit) for predicting purchase intention. Based on the coefficient of determination test, the R2 value of 0.498 indicates that the contribution of independent variables to purchase intention is 49.8%, while the remaining 50.2% is explained by other factors outside the scope of this study